A Decade of Project-Based Learning (PjBL) and Mathematical Problem Solving: Past, Present, and Future Direction - Mamonto, Kamilya Atmaloka; Yaro, Zunia Fila; Fakhriyana, Dina (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2024)
Over the last decade, research related to the impact of implementing the Project-Based Learning (PjBL) model on students' mathematical problem solving abilitiy has been widely published in a number of reputable journals. However, there is still lack of research related to mapping the results of this research which can later provide insight to the researchers and educators, especially teachers, in mathematics learning activities. Therefore, it is necessary to study various research findings that implement the PjBL model which have an impact on students' problem-solving ability. The aim of this research is to obtain information from various research results regarding the impact of implementing the PjBL model on mathematical problem solving ability. Meanwhile, the method used is Systematic Literature Review (SLR) with reference to journal articles published from 2013 to 2023. Furthermore, the keywords used in obtaining this research article are by combining the PjBL model and mathematical problem solving ability with inclusion and exclusion criteria, resulting in 20 journal articles. The research results show that the PjBL model can be applied in mathematics learning and has a positive impact on students' mathematical problem solving ability. Finally, this study contribute as a promising resources to potential research opportunity and significant implification for future research regarding PjBL model and mathematical problem solving ability.